2014
DOI: 10.1016/j.jstrokecerebrovasdis.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Gender Differences in Stroke Severity, Outcomes, and Treatment in Patients with Acute Ischemic Stroke

Abstract: Background Previous research has indicated that women and Blacks have worse outcomes following acute ischemic stroke (AIS). Little research has been done to investigate the combined influence of race and gender in the presentation, treatment and outcome of patients with AIS. We sought to determine the association of race and gender on initial stroke severity, thrombolysis and functional outcome after AIS. Methods AIS patients who presented to two academic medical centers in the United States (2004-2011) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 27 publications
4
73
1
2
Order By: Relevance
“…In previous population-based studies from Europe, casefatality rates at 30 days have been reported to be 20.6-21.6% for total stroke 22,23 and 31.6% for intracerebral hemorrhage. 22 In several recent hospital-based studies, the percentage of patients with death or dependency (mRS score 3 to 6) at discharge has been reported to be 43.4% in men and 49.6% in women for ischemic stroke in the USA, 24 and 30.9% in men and 39.8% in women for total stroke in Korea. 25 In a large-scale Japanese hospital-based registry, the frequency of death or dependency (mRS score 3-6) at discharge has been reported as 45.2% for large-artery infarction, 26.6% for lacunar infarction, 59.5% for cardioembolic infarction, and 67.4% for hypertensive intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…In previous population-based studies from Europe, casefatality rates at 30 days have been reported to be 20.6-21.6% for total stroke 22,23 and 31.6% for intracerebral hemorrhage. 22 In several recent hospital-based studies, the percentage of patients with death or dependency (mRS score 3 to 6) at discharge has been reported to be 43.4% in men and 49.6% in women for ischemic stroke in the USA, 24 and 30.9% in men and 39.8% in women for total stroke in Korea. 25 In a large-scale Japanese hospital-based registry, the frequency of death or dependency (mRS score 3-6) at discharge has been reported as 45.2% for large-artery infarction, 26.6% for lacunar infarction, 59.5% for cardioembolic infarction, and 67.4% for hypertensive intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies demonstrated significant differences in delay to arrival within 3 hours22, 52, 58 that persist after adjusting for age, sex, stroke severity, and insurance status 26. Boehme et al found that black women, specifically, are more likely to arrive outside of the 3‐hour time window than white men, black men, or white women 59. In their analysis of >200 000 acute stroke cases in the Get With The Guidelines Stroke registry, Ekundayo et al found that minorities were less likely to use EMS,12 but in the Greater Cincinnati/Northern Kentucky Stroke Study there was no difference in EMS utilization between white and black patients 60.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown compelling sex, racial, and socioeconomic disparities in the treatment and outcomes among patients with acute stroke. [5][6][7] Generally, racial minorities and women with acute stroke have lower quality hospital care, 5,[8][9][10][11][12][13] including the use of imaging. These disparities can contribute to inequality in stroke outcomes and are a top research priority of the National Institute of Neurologic Disorders and Stroke.…”
mentioning
confidence: 99%